Mental health matters : a mixed-method exploration of attitudes towards psychological services within long-term care facilities - Katla Marín Stefánsdóttir 1996- (2024)
The population of adults aged 60 and older is increasing rapidly. As this demographic grows, so does the demand for care services. Older adults in Long-Term Care Facilities (LTCF) are particularly vulnerable, with 60.0% of residents in Iceland diagnosed with a mental health condition. Addressing barriers to accessing psychological services is critical to ensure they receive comprehensive care. To date, psychological services are not available within LTCF in Iceland. This study aimed to explore attitudes towards psychological services in LTCF in Iceland. Specifically, attitudes were explored by various sociodemographic factors, and prior experience with psychological services. Furthermore, the study explored participants’ reasons for wanting psychological services to be available within LTCF, and identified the services they believed are important for older adults with mental health conditions to have access to. The study design was cross-sectional and mixed methods. Both quantitative and qualitative data were collected and analysed simultaneously. The sample consisted of 200 participants, their age ranged from 21 to 85, with an average age of 46,8 years (SD = 17.02). Results show that the only sociodemographic variable that affected attitude was gender. Despite that, almost all participants were positive towards psychological services and possible services within LTCF. Most participants (96.5%) perceived psychological services to be important within LTCF. Participants expressed positive attitudes towards a variety of psychological services and provided various ideas on how psychological services can be beneficial for the LTCF environment. Future research should directly involve LTCF residents to gain insights into their perspectives on potential services and the specific types of psychological services they deem necessary for their care. Building on this, conducting pilot studies is essential to further investigate the effectiveness of psychological services within LTCF. Keywords: Attitude, older adults, ...